Enhances of Management and Estimated District Expenditure Revenue Given to the Country in the Management of District Development - Indrawan, Muhammad Isa (Budapest International Research and Critics University, 2021)
The Regional Revenue and Expenditure Budget (APBD) is the annual financial plan of the regional government that is approved and discussed jointly by the regional government and DPRD and determined by regional regulations. The Process of Preparation of the Regional Revenue and Expenditure Budget (APBD) Based on Law Number 23 of 2014 concerning Government, in terms of the Concept, Design, and Amendment to the Regional Revenue and Expenditure Budget (APBD). Based on this background, some problems will be discussed, namely, the process of preparing the APBD budget based on Law No. 17 of 2003 concerning State Finances, Preparation of APBD Budget Funds given to sub-districts in the management and development and implementation of the management of APBD funds given to sub-districts in empowering the community in the village of bamboo fields, Medan Tuntungan sub-district. This research is descriptive, using quantitative research type, and using empirical legal research type, while the method used in this research is field research method and data collection techniques used are primary and secondary. In this study, the budgeting process begins with setting goals, targets, and policies. The common perception between various parties about what will be achieved and the relevance of the objectives to the various programs that will be carried out is very crucial for the success of the budget. It is necessary to increase the capacity of Human Resources (HR), especially in terms of using and operating computer facilities used to process and input important data.